The Phoenix Model: disengagement and deradicalisation - Silke, Andrew; Morrison, John; Maiberg, Heidi; Slay, Chloe; Stewart, Rebecca (Centre for Research and Evidence on Security Threats, 2021)
This article provides an introduction to the Phoenix Model of Disengagement And Deradicalisation. In a review of disengagement and deradicalisation literature from 2017 to 2020, we identified 11 major themes: Opportunity, Disillusionment, (Dis)trust, Family and friends, Prison, Identity, Programme interventions, Formers, Security, Mental health, and Reintegration. Many of these themes have been flagged as significant factors in disengagement and deradicalisation before, though this is the first time they’ve been identified as a collective. This systematic approach allowed further analysis to develop a new model for understanding disengagement and deradicalisation processes which is outlined here.
CREST copyright requirements can be found at: https://crestresearch.ac.uk/about/copyright/
Keywords: terrorism; Phoenix Model; disengagement; deradicalisation